The Relationships Between Contextual Variables and Perceived Importance and Benefits of Environmental Management Accounting (EMA) Techniques - EL-Shishini, Hatem Mohamed; Upadhyaya, Makarand (Journal of Environmental Accounting and Management, 2026)
Environmental management accounting (EMA) has emerged over last decades because of increasing awareness of the impacts of companies on their environment. There was a limited attention directed to the importance attached to EMA's techniques and the importance of benefits derived from EMA's techniques. Drawing off the contingency theory literature, the current study examined the relationship between the size, intensity of competition, type of industry, cost structure, and the importance attached to EMA's techniques and the importance of benefits derived from these techniques. Data was collected using a sample of 100 accountants in Bahrain. Replies were received from 36 accountants. The results indicated that there were significant relationships between size, type of industry, cost structure, and the importance attached to EMA's techniques. With regards to the benefits derived from EMA's techniques, the results indicated that the type of industry and cost structure was significantly influencing the importance of benefits of EMA's techniques. The study determined many potentials for future research including understanding factors influencing the allocation of environmental costs to products/services, and using other contextual variables to gain a better understanding of EMA in less developing countries.